THE INFLUENCE OF PERCEIVED ORGANIZATIONAL SUPPORT, JOB EMBEDDEDNESS, AUTHENTIC LEADERSHIP, AND PSYCHOLOGICAL OWNERSHIP ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR IN EMPLOYEES OF THE IT COMPANIES YOGYAKARTA - Dwiyanti, Clarita; Hadi, Syamsul; Kurniawan, Ignatius Soni (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
Organizational Citizenship Behavior (OCB) is a positive deviant behavior that plays an important role in the corporate social aspects such as teamwork, communication, and other interpersonal relationships that have an impact on company productivity. This research aims to examine and analyze the influence of perceived organizational support, job embeddedness, authentic leadership, and psychological ownership on OCB in employees at one of the IT companies Yogyakarta. 124 samples were collected using nonprobability sampling techniques, more precisely purposive sampling. This research method is quantitative by collecting data using a questionnaire. Data analysis using SmartPLS 4.0 version. The research results show that perceived organizational support and authentic leadership have no effect on OCB. However, job embeddedness and psychological ownership have a positive and significant effect on OCB.